Revitalisasi Nilai-nilai Sosial Tauhid dalam Merespons Realitas Kekinian - Ahmad Zainuddin (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article discusses the efforts to revitalize social values on the basis of faith in monotheism that is alienated from social reality. So far, Islamic movement is too normative and tends to neglect differentiation, segmentation and social stratification in society. Consequently, the normative sentiments regarding the unity of the people became much more prominent than the actual commitment to defend the weak, displaced and oppressed groups in society. To understand Islam needs to look at the historical determinism, in order to avoid a partial understanding. Pure and social ritual can be performed equally an ideal personification of a true Muslim. The egalitarian character of Islam as a religion of liberation manifestation should be used to understand human conception and reality. Thus, someone will not be separated from his nature as human being who must worship the Lord and carry out social functions, as well as to avoid the trap of ritual extremism or social extremism. The revitalization of social values of monotheism by integrating relational networks of Islam in social change gave birth to anti ethnocentrism, universalism and liberation.